Scholars who lived in Bukhara region - Boqiyev Azizbek (Periodica Journal, 2023)
This article explores the remarkable legacy of scholars who lived in the Bukhara region, a historical crossroads of cultures and knowledge. Through an examination of their contributions, this study sheds light on the significant role played by Bukhara in the development and dissemination of knowledge during various periods of history. The article employs historical research methods to trace the lives and works of these scholars, drawing on a wide range of primary and secondary sources. The results reveal the profound impact of Bukhara's intellectual heritage on the broader Islamic world and beyond, providing valuable insights into the region's historical significance
Keywords: Bukhara; Scholars; Intellectuals; Golden Age